Evaluating audio-visual falls prevention messages with community-dwelling older people using a World Café forum approach - De Jong, Lex; Francis-Coad, J.; Wortham, C.; Haines, T.P.; Skelton, D.A.; Weselman, Tammy; Hill, Anne-Marie (BMC, 2019)
Background: Falls risk increases sharply with older age but many older people are unaware or underestimate their risk of falling. Increased population-based efforts to influence older people's falls prevention behavior are urgently needed. The aim of this study was to obtain a group of older people's collective perspectives on newly developed prototypes of audio-visual (AV) falls prevention messages, and evaluate changes in their falls prevention behaviour after watching and discussing these.